DEDICATION AND WORKING ITSELF: A NEW WAY TO IMPROVE EMPLOYEE PERFORMANCE IN A DYNAMIC ERA - Muhamad Rustandi; Nurul Hermina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effect of dedication on employee performance with work itself as a mediating variable at PT PLN (Persero) UP3 Semarang. The background of the study is based on the phenomenon of declining employee performance indicated by low discipline, responsibility, and suboptimal work completion. Dedication is seen as an important factor that can encourage employee enthusiasm, responsibility, and commitment to work, while work itself reflects employee perceptions of work that is meaningful, challenging, and provides opportunities for self-development. This study uses a verification method with a quantitative approach. The study population amounted to 120 employees and all were sampled using a saturated sampling technique. Data were collected through questionnaires, interviews, and documentation studies, then analyzed using path analysis with the help of statistical software. The results showed that dedication significantly influenced work itself and employee performance, while work itself also significantly influenced performance. In addition, work itself was proven to mediate the relationship between dedication and performance, although the direct effect of dedication on performance was stronger than the indirect effect through work itself. These findings underscore the importance of human resource management strategies that focus not only on increasing dedication, but also on creating meaningful, challenging work quality and providing development opportunities to support continuous improvement in employee performance